If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-119=-6(8p-3)+7
We move all terms to the left:
-119-(-6(8p-3)+7)=0
We calculate terms in parentheses: -(-6(8p-3)+7), so:We get rid of parentheses
-6(8p-3)+7
We multiply parentheses
-48p+18+7
We add all the numbers together, and all the variables
-48p+25
Back to the equation:
-(-48p+25)
48p-25-119=0
We add all the numbers together, and all the variables
48p-144=0
We move all terms containing p to the left, all other terms to the right
48p=144
p=144/48
p=3
| 11x-1+24=12+13 | | 2(w+3)=6+2w | | 8x2−x+2=2 | | 18+20c=5c-15+18c | | 28=8x+12=7x | | 1x+2x+(x+8)=180 | | m-29=58 | | -3(4x+3)=12x+9 | | 8x^2−x+2=2 | | 5/4=−4c+4/1 | | 9d-9=d-3 | | 2/5x+2/3=4/5 | | 7a+-3=7a-3 | | 2/5=w-2/2 | | -1/2x+3/14=-2/7 | | 2x+9√x-5=0 | | 7(6-12k)-3=-2k-5(11k+3) | | 10+.10x=35 | | 375÷500=t | | x-34=54 | | 4n+3=5/7 | | 4.2x-3=0.5(8.4x=6) | | 13.1w=4.44+14.3w | | x^2+-16x+16=0 | | 2.5(x-2)=5 | | 3x+25=5.50 | | -9x+15=7 | | x/4+16=43 | | 4x+6x=42-4x | | -10=a+10 | | 11x+6(7+4x)=6(6x+8) | | b/2=11 |